Cometabolism of Fluoroanilines in the Presence of 4-Fluoroaniline by Ralstonia sp. FD-1 - Wenling Cao; Erxi Song; Dongsheng Shen; Meizhen Wang (Journal of Chemistry, 2015)
A strain of Ralstonia sp. FD-1 capable of using 4-fluoroaniline (4-FA) as the sole carbon and nitrogen source was investigated for its ability to utilize 4-FA isomers (2-FA, 3-FA) and homologs (2,4-DFA, 3,4-DFA, and 2,3,4-TFA). Both 4-FA and 3-FA could be mineralized as the sole carbon and nitrogen source by FD-1. 2-FA, 2,4-DFA, 3,4-DFA, and 2,3,4-TFA could not be degraded by FD-1, respectively, and were selected as secondary substrates for cometabolism with 500 mg/L 4-FA as growth substrate. Bacterial growth (OD600), F− concentrations, and fluoroanilines contents were measured to determinate the degradation ability of 4-FA isomers and homologs by FD-1. FD-1 growth was inhibited by 2,4-DFA, 3,4-DFA, and 2,3,4-TFA at higher concentrations (400 mg/L), except for 2-FA. Complete fluoroanilines degradation was achieved while incomplete defluorination was characterized by the stoichiometric fluoride release indicating partial degradation but not total mineralization. When fluoroaniline was supplied to the resting cells of strain FD-1, a relatively effective removal was showed. Strain FD-1 had broadened application prospect of toxicity and low nutrition fluoroanilines wastewater.